Упростите выражение:​

0 голосов
13 просмотров

Упростите выражение:​


Алгебра (48 баллов) | 13 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Ответ:Вот держи

Объяснение:


image
(55 баллов)
0

Спс

0 голосов

2a^2 + 2ab + 3b^2 - a^2 - 2b^2 = a^2 + 2ab + b^2 = (a + b)^2

1) 2a^2 - a^2 = a^2.

2) 3b^2 - 2b^2 = b^2

Квадрат суммы (формула сокращенного умножения): a^2 + 2ab + b^2 = (a + b)^2.

Ответ: (a + b)^2.

(22.4k баллов)
0

привет всем

0

есть кто?

0

Здравствуйте, зачем вы сюда пишите?